Compensating Cutting Losses by Passivation Solution for Industry Upgradation of TOPCon and SHJ Solar Cells. Issue 2 (24th November 2022) - Li, Wenheng; Wang, Xiao; Guo, Jianxin; Zhang, Xuning; Chen, Bingbing; Chen, Jingwei; Gao, Qing; Yang, Xueliang; Li, Feng; Wang, Jianming; Song, Dengyuan; Wang, Shufang; et al.
Abstract : The main hurdle to the upgradation of photovoltaic industry is the large performance losses that the tunnel oxide passivated contact (TOPCon) and silicon heterojunction (SHJ) cells have during the cutting and separating process for the assembly of shingle solar panels. Here, an organic solution with the passivation effect is prepared in situ by a non‐vacuum spraying process, which effectively compensates the cutting loss caused by laser slicing technology. Both the open‐circuit voltage ( V oc ) and power conversion efficiency (PCE) are improved. For example, after edge passivation, the V oc and PCE of the 3 × 3 cm 2 SHJ ( K = 1.186%) cell increase by up to 8 mV and a 1–2% in absolute efficiency, respectively. This passivation‐solution based method can be easily integrated into the current production line and thus solve the issue of cutting loss in separated silicon solar cells. This study provides a new passivation technology to compensate the recombination loss on the edge surface caused by the cutting process in shingle solar panels. Abstract : Here, an organic solution with the passivation effect is prepared in situ by spraying process, which effectively compensates for the cutting loss caused by laser slicing technology for tunnel oxide passivated contact and silicon heterojunction silicon solar cells. This study provides a new passivation technology to compensate for the recombination loss on the edge surface caused by the cutting process in shingle solar panels.